Superficial Keratectomy: A Review of Literature - Salari, Farhad; Beikmarzehei, Alireza; Liu, George; Zarei-Ghanavati, Mehran; Liu, Christopher (Frontiers in Medicine, 2022)
Superficial keratectomy (SK) is the manual dissection of the superficial corneal layers (epithelium, Bowman's layer, and sometimes superficial stroma). SK is done using a surgical blade or diamond burr. Some surgeons use intraoperative mitomycin C 0.02% or amniotic membrane transplantation to improve surgical outcomes. This literature review shows that SK remains an effective method for different indications, including tissue diagnosis, excision of corneal degenerations, dystrophies, scarring, recurrent corneal erosions, and retained corneal foreign body.